Terahertz Sensor Study Based on Spoof Surface Plasmon Polaritons - Ruiqi Zhao; Guizhen Lu; Hongcheng Yin; Jingjing Liang; Dongdong Zeng; Huaibao Xiao (International Journal of Antennas and Propagation)
The spoof surface plasmon polaritons (SSPPs) structure can be used as a sensor in THz region for the biosensing. The accuracy of resonance and amplitude for sensor is very important for biosensing. The momentum matching of SSPPs determines the resonance position and the gap distance determines the amplitude. For the biomolecular sensing, the sample is positioned between the prism base and the SSPPs structure. The momentum matching condition at the current study does not consider the effect of sample refractive index and the resonance position has a significant error. Here the correction is made to the momentum matching condition which considers the effect of the sample refractive index. A comparative study of surface plasmon resonance (SPR) sensing performance based on frequency and angle variations shows that the sensing sensitivity for frequency region is superior to that of angle region; in the meanwhile, as an application of biosensors, we have detected different types of brain lesions in the frequency range. Furthermore, the reflection amplitude is related to gap size between the prism and SSPPs. The relationship of gap size and reflection amplitude is studied. By using the relationship between gap size and reflection amplitude, the amplitudes at different frequencies or incident angles for different refractivities have the same reflection dips compared to the other published results. The simulation is performed and the results proved the theory.